Physical, chemical, and sensory characteristics of pumpkin jam with porang flour addition - Nurrahman Nurrahman; Wan Ezie Adila; Lukman Hakim Safian; Sukes Lindaningsih; Septi Ana Purnamasari; Risma Nurul Azizah; Agus Suyanto; Wikanastri Hersoelistyorini; Nurhidajah Nurhidajah; Yunan Kholifatuddin Sya'di; Diode Yonata (AGROINTEK, 2025)
Food processing is a way to extend the shelf life of products. In Indonesia, pumpkin and porang orange tubers are abundantly available and underutilised, but they have the potential to be developed into a local food-based product. Diversifying processed pumpkin into jam is a functional food alternative with high nutritional value. Porang flour is a thickener in foods and beverages that can stabilise the gel structure. This study aimed to determine pumpkin jam's physical, chemical, and sensory characteristics after adding porang flour. The stages of making pumpkin jam begin with making pumpkin puree, first cooking, mixing, second cooking and checking pH, then analysing physical characteristics (total soluble solids, spreadability, viscosity, and colour), chemical analysis including water content, antioxidant activity, total phenols, vitamin E, crude fibre and sensory properties. Variations of porang flour addition to pumpkin jam were (0; 0.5; 1; 1.5; and 2%). The results showed that adding porang flour influenced the physical characteristics, antioxidant activity, total phenols, vitamin C, and crude fibre of pumpkin jam but had no effect on water content and vitamin E. Adding porang flour up to 2% gave a good taste of pumpkin jam.